2020
DOI: 10.20344/amp.14222
|View full text |Cite
|
Sign up to set email alerts
|

Population-based Estimates for High Risk of Severe COVID-19 Disease due to Age and Underlying Health Conditions

Abstract: Introduction: COVID-19 is a viral respiratory disease, which became a global threat to public health. Specific subsets of the population are more vulnerable, namely those with chronic diseases. We aimed to estimate the share of the Portuguese population at the highest risk for complications following COVID-19 infection due to both old age and specific comorbidities.Material and Methods: Our sample included all people aged 65 years and above (2215 men and 3486 women) who participated in the fifth Portuguese Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…As a result, a number of environmental and anthropogenic factors were identified as potential drivers. Namely clinical-epidemiological conditions (Bai et al, 2020;Guan et al, 2020), climatic conditions (Chan et al, 2011;Paez et al, 2020;Quilodrán et al, 2020), socioeconomic and demographic structure (Laires and Nunes, 2020;Maroko et al, 2020;Marques, 2020;Murgante et al, 2020;Roy et al, 2020;Prazeres et al, 2021) and human mobility patterns (Chen et al, 2020;Melo et al, 2020;Orea and Álvarez, 2020;Tamagusko and Ferreira, 2020). These associations provide information on possible mechanisms by which the spread or impact of COVID-19 is hampered or magnified, in turn assisting the design of preventive or mitigation measures.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a number of environmental and anthropogenic factors were identified as potential drivers. Namely clinical-epidemiological conditions (Bai et al, 2020;Guan et al, 2020), climatic conditions (Chan et al, 2011;Paez et al, 2020;Quilodrán et al, 2020), socioeconomic and demographic structure (Laires and Nunes, 2020;Maroko et al, 2020;Marques, 2020;Murgante et al, 2020;Roy et al, 2020;Prazeres et al, 2021) and human mobility patterns (Chen et al, 2020;Melo et al, 2020;Orea and Álvarez, 2020;Tamagusko and Ferreira, 2020). These associations provide information on possible mechanisms by which the spread or impact of COVID-19 is hampered or magnified, in turn assisting the design of preventive or mitigation measures.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In addition, COVID-19 has already been shown to impact individuals with certain preexisting health conditions at a greater rate. 15 Both federal and state policymakers looked to Medicaid as a central tool in their response to the national emergency. 16 However, whether differences exist in COVID-19 outcomes between communities of Medicaid and non-Medicaid expansion states remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, while some of these epidemiological findings have been previously recognized [8,24], other aspects relating to multimorbidity and COVID-19 addressed in the present study are new or less well described, and, at the same time, they answer to previously identified gaps in the research [18], such as considering not only underlying conditions but also sociodemographic factors [8] and clinical characteristics.…”
Section: Discussionmentioning
confidence: 52%
“…This observed high prevalence was not unexpected. It was previously suggested that 22% of individuals worldwide may be at increased risk of severe COVID-19 [8], and in Portugal, 15.5% of the population might be at high risk for complications from COVID-19 according to the 2014 Portuguese National Health Interview Survey [24]; therefore, it is likely that higher frequencies will be found in chronic adult individuals, as is the case of the population of the present study.…”
Section: Discussionmentioning
confidence: 62%